PENERAPAN MEDIA PEMBELAJARAN “ULAR TANGGA” DALAM MENINGKATKAN PENGUASAAN KOSAKATA BAHASA ARAB - Nazahah Ulin Nuha; Itsna Mayfatul Chasanah (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2022)
The application of learning media "snakes and ladders" on vocabulary mastery is an appropriate idea in learning Arabic which is very suitable for use at the elementary school level. Mastery of vocabulary in learning the basic potential for learning foreign languages. One of the learning media that can support or that can help improve the mastery of Arabic vocabulary is the snake and ladder learning media. This study aims to facilitate the learning process at Madrasah Ibtidaiyah An-Nur Turen in mastering vocabulary so that learning becomes fun and uncluttered and can achieve the desired goals. In this study, researchers used qualitative methods. With data collection techniques through observation, interviews, documentation and tests at the end. The final result in the application of snake and ladder learning media in calculating the t-test in the control group with an average of 51.00, an average difference of 7.50, and a t-count of -5.582. While the results of vocabulary mastery in the calculation of the t-test in the experimental group with an average of 70.6, an average comparison of 15.00, and a t-count of -11.225. So with this, it can be concluded that learning with snakes and ladders media is effective in learning Arabic in terms of vocabulary mastery.Keywords: learning media, snakes and ladders, Arabic vocabulary